Pemberdayaan Perempuan Melalui Pelatihan Keterampilan Membuat Hantaran dan Seserahan Pernikahan Di RT II RW V Desa Ridan Permai Bangkinang - Rahmad Akbar; Dzulhijjah Yetti; Merlia Rahmayani; Nurbit Nurbit; Harmi Yelmi (Politeknik Kampar, 2024)
This initiative takes place in RT II RW V of Ridan Permai Village. Typically, homemakers with idle hours between caring for their families have inspired us to create a program focused on Training in Crafting Wedding Gifts and Dowries. This initiative serves as a potential side hustle for these housewifes, allowing them to use their newfound skills to generate additional income. The primary goal is to empower housewifes to explore independent service ventures, equip them with skills, and boost their individual and collective earnings. The implementation methods include lectures/discussions, skills training/workshops, and mentoring.